2009
DOI: 10.1177/0040517509104275
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Stitched Layered Aramid Woven Fabric Structures and their Experimental Characterization of Ballistic Performance

Abstract: The aim of the research was to develop light and enhanced energy absorbed layered ballistic structures. For this reason, various ballistic structures were developed. These structures form two groups: multiaxially stitched and unstitched. Each group further consists of four structure types: (i) 14-layer Kevlar 29 woven fabric; (ii) 14-layer Kevlar 129 woven fabric; (iii) 7-layer Kevlar 29 fabric and 7-layer Kevlar 129 fabric; and (iv) 12-layer Kevlar 29 fabric oriented with respect to basic fabric direction at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 15 publications
0
22
0
3
Order By: Relevance
“…The Kevlar Ò K129 fiber has an areal density of around 185 g/m 2 compared to 270 g/m 2 for the Kevlar Ò K29 fiber, but has a strength which is 40% higher than that of the Kevlar Ò K29 fiber (used for the PASGT helmet). The Kevlar Ò K129 fiber also has a higher energy absorption capacity than the Kevlar Ò K29 fiber [12]. The ACH thus has a higher ballistic and impact protection capability than the PASGT helmet at a smaller weight.…”
Section: Modular Integrated Communications Helmet and Advanced Combatmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kevlar Ò K129 fiber has an areal density of around 185 g/m 2 compared to 270 g/m 2 for the Kevlar Ò K29 fiber, but has a strength which is 40% higher than that of the Kevlar Ò K29 fiber (used for the PASGT helmet). The Kevlar Ò K129 fiber also has a higher energy absorption capacity than the Kevlar Ò K29 fiber [12]. The ACH thus has a higher ballistic and impact protection capability than the PASGT helmet at a smaller weight.…”
Section: Modular Integrated Communications Helmet and Advanced Combatmentioning
confidence: 99%
“…Thermoplastics for ballistic applications have been studied extensively [12,150,151]. Both manufacturing and design aspects of thermoplastics were investigated in Walsh et al [150,151], where various Kevlar Ò fiber-thermoplastic matrix systems were explored.…”
Section: Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber properties are shown in Table 1 with other fibers and materials generally used in ballistic areas. 23,24 3D woven carbon/epoxy composite 3D orthogonal woven preform had three yarn sets as warp, filling and z-yarns. These sets of yarns were all interlaced to form the structure where warp yarns were longitudinal and the others were orthogonal.…”
Section: Methodsmentioning
confidence: 99%
“…22 Studies also showed that multidirectional stitched multilayered Kevlar woven fabric structures had low back face signature compared to that of the unstitched structures. 23 The objective of this study is to develop light and ballistically enhanced structures which can withstand high impact load using the insight of previous work in which material properties were investigated in terms of structural and processing parameters, and experimentally understand the ballistic failure in the structure upon impact.…”
Section: Introductionmentioning
confidence: 99%